Pediatric laparoscopic pyeloplasty of pelvic ectopic kidney with UPJO - A case report - Ergashev, Kobiljon (Urol Case Rep, 2020)
Prevalence of pelvic ectopic kidney with obstruction is not common. Associated anomalies may produce technical difficulties and surgical challenges in treatment. Diagnostic tools such as USG KUB, renal scintigraphic studies (DMSA, DTPA), MRI, and preoperative RGP are very informative examinations to properly decide the timing of the operation and method of it. The patient was under close surveillance from the detection of antenatal hydronephrosis until the development of UPJ obstruction. Herein, we report the case of a patient with this anomaly who successfully underwent laparoscopic reconstruction.